Pippi goes to school - Lindgren, Astrid, 1907-2002.; Chesworth, Michael (New York : Puffin Books, 1999)
After Tommy and Annika entice Pippi into going to school, her first-and-only day there is unlike anything they ever expected.
820
Keywords: First day of school -- Fiction; Schools -- Fiction; Humorous stories; Sweden -- Fiction